Nano Online 2018
DOI: 10.1515/nano.0034.00139
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanomaterials and their application to electrochemical sensors: a review

Abstract: Carbon has long been applied as an electrochemical sensing interface owing to its unique electrochemical properties. Moreover, recent advances in material design and synthesis, particularly nanomaterials, has produced robust electrochemical sensing systems that display superior analytical performance. Carbon nanotubes (CNTs) are one of the most extensively studied nanostructures because of their unique properties. In terms of electroanalysis, the ability of CNTs to augment the electrochemical reactivity of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 205 publications
0
2
0
Order By: Relevance
“…Compared with other materials, carbonaceous nanostructures offer simple processes for manufacturing while maintaining a minimal number of defects. The most common carbon allotropes such as graphene, carbon nanotubes (CNTs), carbon dots, carbon nanofibers and nanodiamonds (NDs) provide chemical inertness, a relatively wide potential window, and low background currents; these allotropes are suitable for various analytes [22,23]. In their shade are still less popular structures resembling multi-layer fullerenes called carbon nanoonions (CNOs).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other materials, carbonaceous nanostructures offer simple processes for manufacturing while maintaining a minimal number of defects. The most common carbon allotropes such as graphene, carbon nanotubes (CNTs), carbon dots, carbon nanofibers and nanodiamonds (NDs) provide chemical inertness, a relatively wide potential window, and low background currents; these allotropes are suitable for various analytes [22,23]. In their shade are still less popular structures resembling multi-layer fullerenes called carbon nanoonions (CNOs).…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials are very attractive in this area because they have a large surface area to volume ratio, permitting the surface to be used in an efficient way. It was reported that carbon nanomaterials can provide electrochemical biosensing for effective discovery of diseases such as cancers (Power, Gorey, Chandra, & Chapman, ).…”
Section: Introductionmentioning
confidence: 99%